Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.5603/gp.a2021.0183
|View full text |Cite
|
Sign up to set email alerts
|

Mode of vaginal delivery in breech presentation and perinatal outcome

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Obstetrics is a profession of high professional and forensic risk, and numerous forensic reports and expertise emphasize constant basic and constant "refresh" education as the basis for preventing unwanted events and thus preserving the dignity of the professionalism of obstetrics [1][2][3][4]. Thus, recent works indicate a significant reduction of birth injuries in SD with continuous training of skills [1][2][3][4][5][6][7][8][9], as well as in VBD [10][11][12][13][14], with the desire and will to improve skills, especially in the delivery of twins and VBD, although with a smaller share due to insufficient numbers according to a recent New Zealand study [14]. Also, there are articles by Swiss authors who critically processed the monitoring and interpretation of the learning curve of residents from performing CS, as well as basic abdominal operations in obstetrics [15], and Soergel et al [16] presented article in which they found that experience during CS reaches a plateau after 10-15 CS, however, they emphasize that the learning process is highly individualized and difficult to predict, so supervision and evaluation of the resident by an experienced surgeon is important.…”
Section: Discussionmentioning
confidence: 99%
“…Obstetrics is a profession of high professional and forensic risk, and numerous forensic reports and expertise emphasize constant basic and constant "refresh" education as the basis for preventing unwanted events and thus preserving the dignity of the professionalism of obstetrics [1][2][3][4]. Thus, recent works indicate a significant reduction of birth injuries in SD with continuous training of skills [1][2][3][4][5][6][7][8][9], as well as in VBD [10][11][12][13][14], with the desire and will to improve skills, especially in the delivery of twins and VBD, although with a smaller share due to insufficient numbers according to a recent New Zealand study [14]. Also, there are articles by Swiss authors who critically processed the monitoring and interpretation of the learning curve of residents from performing CS, as well as basic abdominal operations in obstetrics [15], and Soergel et al [16] presented article in which they found that experience during CS reaches a plateau after 10-15 CS, however, they emphasize that the learning process is highly individualized and difficult to predict, so supervision and evaluation of the resident by an experienced surgeon is important.…”
Section: Discussionmentioning
confidence: 99%